Reframing China in U.S. Trade policy discourse: a context-deictic space model for ideological positioning - Hu, Ying; Li, Hongfei (Frontiers in Communication, 2025)
U.S.-China trade tensions have reshaped global economic relations and produced a discursive struggle over identity, threat, and legitimacy. While research in Critical Discourse Analysis (CDA) and Critical Cognitive Linguistics (CCL) has examined ideological framing, few studies have systematically modeled how diplomatic discourse constructs shifting representations over time. This study proposes the Context-Deictic Space Model (CDSM), a socio-cognitive framework integrating van Dijk’s Context Model with Chilton’s Deictic Space Theory. By mapping participants, settings, and events onto spatial, temporal, and axiological axes, CDSM visualizes ideological positioning in discourse. Applied to three U.S. trade policy agendas (2017–2019), the analysis shows how China is reframed from a distant trade partner to a proximate adversary, invoking crisis and legitimizing protectionism while marginalizing actors like the World Trade Organization (WTO). Theoretically, the study extends CCL by offering a visualizable model of ideological distance; empirically, it provides a new lens for analyzing threat construction in political discourse.